Intra - National Cultural Values : A Systematic Review of Literature and the Way Forward for Comparative Studies in India - Choudhary, Jugal; Shree, Sonal (Prabandhan: Indian Journal of Management, 2021)
The purpose of this paper was to seek productive directions for intra - national comparison of cultural values in a diverse country such as India. We conducted a systematic review of peer-reviewed literature about subcultures within nations. The review indicated increasing interest in studies of intra-nation cultures. It also demonstrated that more needs to be done in the area of comparing cultural values at the intra-nation level, particularly in diverse non - Western countries. The review indicated the following features as desirable in such research, to make it useful to management : Compare geographic units. Select values purposefully based on relevance to management. Use survey as the source of data. Use scales that are as similar to those used in inter - nation studies as practical. Report findings as mean scores, ranks, plots, or comparison of pairs. Include at least one country-level data point to serve as a reference for a non-domestic audience.